2022
DOI: 10.1177/09564624221144489
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between raltegravir trough plasma concentration and virologic response and the impact of therapeutic drug monitoring during pregnancy

Abstract: Background Limited data is available on raltegravir (RAL) pharmacokinetics during pregnancy and the value of therapeutic drug monitoring (TDM) in pregnancy is unknown. This study aims to describe RAL trough plasma concentrations (Ctrough) during pregnancy and review the impact of RAL TDM on outcomes. Methods Women from the prospective mother-infant HIV cohort of Mother and Children’s Infectious Diseases Center who received RAL during their pregnancy between 2011-2020 were included. TDM reports were reviewed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…A recent study demonstrated that an RAL trough concentration of 40 ng/mL or higher is a predictor of virological response in pregnant women, and only 3 patients in the third trimester of pregnancy did not reach this threshold. 25 The RAL concentrations during the third trimester of gestation in pregnant women living with HIV were similar to those obtained during the postpartum period. In addition, the standard dose of 400 mg twice daily was capable of maintaining an HIV RNA viral load lower than 50 copies/mL closest to delivery, and no newborn was infected by the virus.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A recent study demonstrated that an RAL trough concentration of 40 ng/mL or higher is a predictor of virological response in pregnant women, and only 3 patients in the third trimester of pregnancy did not reach this threshold. 25 The RAL concentrations during the third trimester of gestation in pregnant women living with HIV were similar to those obtained during the postpartum period. In addition, the standard dose of 400 mg twice daily was capable of maintaining an HIV RNA viral load lower than 50 copies/mL closest to delivery, and no newborn was infected by the virus.…”
Section: Discussionsupporting
confidence: 63%
“…A recent study demonstrated that an RAL trough concentration of 40 ng/mL or higher is a predictor of virological response in pregnant women, and only 3 patients in the third trimester of pregnancy did not reach this threshold 25 . The RAL concentrations during the third trimester of gestation in pregnant women living with HIV were similar to those obtained during the postpartum period.…”
Section: Discussionmentioning
confidence: 65%